(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the origin of Naqshbandii-Mujaddidi and its spread in Central Asia. The main peculiarities and significance of Naqshbandii-Mujaddidi are also elucidated in this article. The analyses of the role of righteous path in the spiritual life of community are given.